1994
DOI: 10.1111/j.1651-2227.1994.tb18093.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular complications in young adults with insulin‐dependent diabetes mellitus since childhood

Abstract: A cross-sectional study in 80 insulin-dependent diabetic patients born 1963-1968 who experienced the onset of diabetes before 15 years of age showed that at a mean age of 21.6 (range 17-25) years and after a mean duration of diabetes of 13.3 (range 6-24) years, 80% of the patients had retinopathy: 70% had background and 10% proliferative changes. Retinopathy correlated with the duration of the diabetes and poor glucose control at 15 years of age but not with the actual level of glycated haemoglobin. The severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…7, 2004 Brought to you by | University of California -San Francisco Authenticated Download Date | 2/20/15 2:37 PM 6-10 years, to 58% with duration >15 years. European studies on cohorts with greater DM duration have reported prevalences ranging from 60-80% at duration 13 years to 100% at duration 20 "^, 18,21 years They used fundus photographs for diagnosis, a method more sensitive than the direct ophthalmoscopy used by us or the indirect ophthalmoscopy used by Ramachandran et al I6 .…”
Section: Discussionmentioning
confidence: 99%
“…7, 2004 Brought to you by | University of California -San Francisco Authenticated Download Date | 2/20/15 2:37 PM 6-10 years, to 58% with duration >15 years. European studies on cohorts with greater DM duration have reported prevalences ranging from 60-80% at duration 13 years to 100% at duration 20 "^, 18,21 years They used fundus photographs for diagnosis, a method more sensitive than the direct ophthalmoscopy used by us or the indirect ophthalmoscopy used by Ramachandran et al I6 .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and progression of DR are highest in the diabetics diagnosed before the age of 30 yr and the increased risk of proliferative diabetic retinopathy (PDR) is associated with more severe retinopathy and clinically significant DME at baseline (1). In particular, 80% of young type 1 patients taking insulin have a clinically evident retinopathy 13 yr after onset of diabetes and the proportion approaches 100% after 20 yr, with a progression to PDR in about 30% of cases (5). However, DR is rarely detected in prepubescent children (6); in fact, the years before the growth spurt do not appear to play a major role in relating duration of the disease to the incidence of retinopathy.…”
Section: Epidemiologymentioning
confidence: 99%
“…Patient age, younger age at diagnosis, longer duration of diabetes (5, 14) high glycosylated hemoglobin (HbA1c) (15, 16) and low C‐peptide levels (17), insulin therapy, presence of microalbuminuria (18, 19) and smoking (19) are also statistically significant indicators of a higher risk for retinopathy. On the contrary, myopia, has been found to be protective in younger‐onset diabetes (20, 21).…”
Section: Epidemiologymentioning
confidence: 99%
“… 12 Whether gender and race are risk factors for PDR remains controversial and requires further research. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…12 Whether gender and race are risk factors for PDR remains controversial and requires further research. 13,14 Although extensive studies have examined the epidemiology of diabetes and its association with DR, as well as the general outcomes of surgical treatment of PDR, few studies have focused on the prognosis of surgical outcomes and risk factors in patients with early-onset T2D. Therefore, it is still unclear whether the clinical presentation and the outcomes of vitrectomy, in terms of PDR complications, differ between young and older T2D patients.…”
Section: Introductionmentioning
confidence: 99%